Polymers for electricity and electronics : materials, properties, and applications - Drobny, Jiri George (Hoboken, N.J. : John Wiley & Sons, 2012)
'This book introduces readers to the fundamentals, basic principles, properties, and applications of electrical polymers. It provides the principles in an extended and accessible way, as well as including examples of state-of-the-art scientific issues. The book evaluates emerging technologies such as light emitting diodes, soft electronics, and conductive fibers used for smart clothing or electromagnetic shields, and explains the advantages of conductive polymers as well as their processibility and commercial use. The coverage includes problems for study with solutions within chapters on chemical and physical properties and basic concepts'--
Includes bibliographical references and index.
Keywords: Electronic apparatus and appliances -- Materials; Polymers